Beyond the Aestheticization of Modern Ruins: The Case of ’Incompiuto Siciliano’ - Arboleda, Pablo (Journal of Contemporary Archaeology, 2016)
The modern Italian landscape includes a large number of public construction projects begun over the past 50 years but abandoned before completion—a testament to the misuse of public funds through political corruption and the influence of the Mafia. Since 2007, a group of artists named Alterazioni Video has been developing the project Incompiuto Siciliano, through which they have sought to counter the negative perception of these ruins by considering them as an aestheticized architectural style. The group’s approach is significant because visual arts, and especially photography, have in recent years been accused of pursuing a merely romanticizing objective that ignores the political, economic and social contexts in which modern ruins arise. Embedding the current paper within this discussion makes it possible to align Incompiuto Siciliano with literatures on contemporary archaeology that regard the aestheticization of ruins as a first step to a critical comprehension of the reasons behind their origination—which ultimately leads to their re-valorization and eventual re-activation.